Does the Medicare Part D Decision‐Making Experience Differ by Rural/Urban Location?. Issue 1 (16th February 2016) - Henning‐Smith, Carrie; Casey, Michelle; Moscovice, Ira
Abstract: Purpose: Although much has been written about Medicare Part D enrollment, much less is known about beneficiaries' personal experiences with choosing a Part D plan, especially among rural residents. This study sought to address this gap by examining geographic differences in Part D enrollees' perceptions of the plan decision‐making process, including their confidence in their choice, their knowledge about the program, and their satisfaction with available information. Methods: We used data from the 2012 Medicare Current Beneficiary Survey and included adults ages 65 and older who were enrolled in Part D at the time of the survey (n = 3, 706). We used ordered logistic regression to model 4 outcomes based on beneficiaries' perceptions of the Part D decision‐making and enrollment process, first accounting only for differences by rurality, then adjusting for sociodemographic, health, and coverage characteristics. Findings: Overall, half of all beneficiaries were not very confident in their Part D knowledge. Rural beneficiaries had lower odds of being confident in the plan they chose and in being satisfied with the amount of information available to them during the decision‐making process. After adjusting for all covariates, micropolitan residents continued to have lower odds of being confident in the plan that they chose. Conclusions: Policy‐makers should pay particular attention to making information about Part D easily accessible for all beneficiaries and to addressing unique barriers that rural residents have in accessing information while making decisions, such as reduced Internet availability. Furthermore, confidence in the decision‐making process may be improved by simplifying the Part D program.